(untitled) (Perner’s Contacts, 2009)
Safety transport of dangerous goods is affected by numbers of factors. The most important are human factors, vehicles, environment and others. There are some factors specially solved in the article. The main preventive activity must be nullify any hazard of carriage of dangerous goods.